Copper‐Catalyzed C−S Coupling of Quaternary Ammonium Salts and Dialkylcarbamodithioic Acid Salts. Issue 5 (20th April 2020) - Chen, Hongyi; Zhang, Qiaoling; Zheng, Wenting; Yang, Hongqin; Zeng, Qingle
Abstract: An efficient synthesis of (chiral) alkyl dialkylcarbamodithioates via a CuI‐catalyzed C−S cross‐coupling reaction of (chiral) quaternary ammonium salts and (chiral) dialkylcarbamodithioic acid salts has been developed. C−S coupling products were obtained with extremely high ee values and yields, with enantioenriched arylmethyl trimethylammonium triflates affording the inverse absolute configuration. Abstract : An efficient synthesis of (chiral) alkyl dialkylcarbamodithioates via the CuI‐catalyzed C−S cross‐coupling reaction of (chiral) quaternary ammonium salts and (chiral) dialkylcarbamodithioic acid salts has been developed. C−S coupling products were obtained with values and yields, with enantioenriched arylmethyl trimethylammonium triflates affording the inverse absolute configuration.